Penerapan Pasal 8 Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen terhadap Beras Tidak Layak Konsumsi - Evinda Nolinia Gulo; Henry Arianto (Jurnal Hukum Lex Generalis, 2026)
The impelemetation of Article 8 of Law Number 8 of 1999 about Consumer Protection (UUPK) with relation to subpar circulation in Indonesia is examined in this paper. Rice adulteration persists despite legal bans, causing conflict between das sollen and das sein. This study looks at five documented cases (2022-2025) using normative legal research with statutory, consequential and case-based techniques. Results show that inadequate distribution control and scattered sanctions after the Job Creation Law (2020) continue to make Article 8 UUPK enforcement unsatisfactory. The study contends that rather than reflecting Rechtsstaat responsibility, state monitoring indicates an achtsstaat attitude. By providing a Machtsstaat-Rechtsstaat analytical paradigm relevant to food distribution recommendations to increase state accountability in protecting consumers' entitlement to safe food, this paper advances the development of consumer protection law.